PENGARUH JENIS PELARUT TERHADAP AKTIVITAS ANTIBAKTERI EKSTRAK DAGING DAN BIJI BUAH BINTARO (Cerbera manghas L.) (Effect of Solvent Types On Antibacterial Activity of Bintaro (Cerbera mangas L.) Meat and Seeds Extract) - Samsul Rizal; Hartami Dewi; Tanto Pratondo Utomo (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
Bintaro fruit is a tropical plant that is widely grown in Indonesia, but it has not been utilized optimally.  Seed of bintaro fruit contains saponin steroids and fatty acids such as palmitat, stearat, oleat, miristat, linolenat, and linoleat fatty acid.  Kernel of bintaro fruit contains saponin and polifenol that are toxic for the pests and insects.  Kernel and seed of bintaro fruit may contain antibacterial activity.  Fatty acid content of bintrao fruit was influenced by level of its maturity, more mature contains more fatty acid.  The purpose of this research is to determine the most suitable solvent to produce the best extract which has activity of anti bacteria and find out the level of anti bacteria activity which is produced from seed and kernel extracts from the bintaro fruit by using difusi agar method.  This research was arranged in a Complete Randomized Block Design, two factorial with four replications.  The first factor was different part of the fruit: seed and kernel.  The second factor was different type of solvent: ethyl acetate, hexane and aquades.  The data were analyzed using Bartlett test for homogeneity and Tuckey test for additivity.  The data then were analyzed using Anova to see the differences between treatments and tested further using LSD of 5% level to determine the best treatment. The result of this research indicated that the kernel of bintaro fruit extracted with ethyl acetate produced the extract which has the highest resistant zone activity of anti bacteria (about 10,95 mm), categorized as an average activity of antibacterial, while bintaro seed extraxted with hexane has less active of antibateria (about 8,43 mm).  The most sensitive bacterium againts seed extracts and kernel of bintaro was Staphylococcus aureus.Keywords : antibacteria, bintaro fruit, extraction, and organic solvents